The Implementation of the MBKM Curriculum in the Nursing Education Study Program at STIKes BudiLuhur Cimahi - Simanjuntak, Damai Yanti; Oktri, Yosi; Sulastini, Rita (IKIP Siliwangi Bandung, 2024)
The MBKM program was launched to prepare graduates who are strong in facing rapid changes in the era of revolution 4.0 such as social, cultural changes, the world of work and increasingly developing technology (Arif Kurniawan & Falah, 2023). The aim of this research is to determine the implementation of the MBKM curriculum in the Budi Luhur Cimahi STIKes Nursing Education Study Program. This research used a descriptive method involving all students who had participated in the MBKM program within the Budi Luhur Cimahi STIKes Nursing Education Study Program. This research used in-depth interview techniques conducted with students, supervisors and the head of the Budi Luhur Cimahi Nursing Education Study Program at STIKes Budi Luhur Cimahi. The conclusion from the research results shows that the implementation of the MBKM Curriculum in the Nursing Education Study Program at STIKes Budi Luhur Cimahi supports the quality of higher education. The aim is to improve the quality of graduates, prepare for the challenges of the complex world of work, and strengthen collaboration with industry. Challenges such as lecturer readiness, resources, coordination, learning culture, and curriculum adjustments are overcome by increasing capacity, optimizing resources, strengthening coordination, student motivation, evaluation, and monitoring. High commitment creates a quality learning environment and graduates who are globally competitive.